PRESUPOSISI DALAM FILM â€œBEAUTY AND THE BEASTâ€ KARYA STEPHEN CHBOSKY DAN EVAN SPILIOTOPOULOS (ANALISIS PRAGMATIK) - HILLARY, TICOH GLORIVIA; KODONG, FENTJE; MITCHEL, HELDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research entitled â€œPresuppostion In The Film â€œBeauty And The Beastâ€ By Stephen Chbosky and Evan SpilotopoulosÂ  (Pragmatics Analysis). This research isÂ  an attempt identify and analyze the types and meanings of presupposition in the film â€˜Beauty and the Beastâ€™. In this research, the writer used descriptive method which analyze based on the theory of George Yule about the types of presupposition and the meanings of presupposition in the film beauty and the beast. In this research, the writer used the types and the meaning of presupposition based on George Yule theory. According to Yule 1996, there are six types of presupposition, they are : Existential presupposition, Factive presupposition, Lexical presupposition, Structural presupposition, Non- factive presupposition, and Counterfactive presupposition. The lexical presuppotion is to much found in this research. ___________________Keywords : Pragmatics, Presupposition, Beauty and the Beast film.